A missed cornual ectopic pregnancy: a case report - Prah, James K.; Derkyi-Kwarteng, Leonard (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ectopic pregnancies continue to be among the leading causes of maternal mortality globally. Cornual pregnancies are types of ectopic pregnancies that occur in the interstitial part of the fallopian tube and invades the uterine wall. We report a case of cornual ectopic pregnancy at 26 weeks that was missed and only diagnosed at autopsy following rupture and death of the pregnant woman. This case emphasizes the importance of a detailed carefully performed ultrasonography in the first trimester for all pregnant women.